2024
DOI: 10.1007/s00262-023-03585-2
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling T cell exhaustion in the immune microenvironment of osteosarcoma via single-cell RNA transcriptome

Debin Cheng,
Zhao Zhang,
Dong Liu
et al.

Abstract: Osteosarcoma (OS) represents a profoundly invasive malignancy of the skeletal system. T cell exhaustion (Tex) is known to facilitate immunosuppression and tumor progression, but its role in OS remains unclear. In this study, single-cell RNA sequencing data was employed to identify exhausted T cells within the tumor immune microenvironment (TIME) of OS. We found that exhausted T cells exhibited substantial infiltration in OS samples. Pseudotime trajectory analysis revealed a progressive increase in the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…Using single-cell sequencing technology, another observational study revealed that exhausted T cells exhibited substantial infiltration and a progressive increase in expression of CTLA4 in osteosarcoma samples. ( 31 ). An experimental study found that infection upregulates the inflammatory immune response mediated by canine macrophages, counteracting osteosarcoma-induced immune suppression through increasing CD80 expression ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Using single-cell sequencing technology, another observational study revealed that exhausted T cells exhibited substantial infiltration and a progressive increase in expression of CTLA4 in osteosarcoma samples. ( 31 ). An experimental study found that infection upregulates the inflammatory immune response mediated by canine macrophages, counteracting osteosarcoma-induced immune suppression through increasing CD80 expression ( 32 ).…”
Section: Discussionmentioning
confidence: 99%